No association between 25-hydroxyvitamin D levels and prediabetes in Brazilian patients. A cross-sectional study - Guilherme de Vieira Giorelli; Lívia Nascimento de Matos; Amir Saado; Vera Lúcia Soibelman; Cristiane Bitencourt Dias (São Paulo Medical Journal)
CONTEXT AND OBJECTIVE: Several studies have evaluated the role of low 25-hydroxyvitamin D (25OHD3) in the pathogenesis of type 2 diabetes (T2DM) and have presented controversial results. The metabolic processes that culminate in T2DM begin under prediabetic conditions. Our aim was to analyze the association between 25OHD3 and glucose metabolism in individuals who were free from but at elevated risk of diabetes. DESIGN AND SETTING: Cross-sectional study at a tertiary hospital. METHODS: Anthropometric and laboratory profiles were determined in patients with one or more of the following risk factors: hypertension; body mass index (BMI) ≥ 25 kg/m2; waist circumference > 80 cm for women and > 94 cm for men; first-degree relatives with diabetes; women with large-for-gestational-age newborns or with gestational T2DM; HDL-cholesterol (high density lipoprotein) < 35 mg/dl; and triglycerides > 250 mg/dl. The patients were divided into two groups: one with prediabetes (abnormal fasting plasma glucose or oral glucose tolerance test) and the other with normal glucose (euglycemic). RESULTS: There was no statistically significant difference between the prediabetic group (n = 38) and euglycemic group (n = 15) regarding age (66.4 ± 10.6 versus 62.6 ± 9.1 years), gender (52.6 versus 73.3% female) and BMI (30.1 ± 4.61 versus 27.9 ± 4.7 kg/m2). Low serum levels of 25OHD3 were found in both groups, without any statistically significant difference between them (29.1 ± 11.8 versus 26.87 ± 9.2 ng/dl). CONCLUSION: There was no association between 25OHD3 levels and the clinical or laboratorial variables analyzed.